Cost-Effective Retrofitting Method for Dry-Stack Masonry Walls Using Fiber-Reinforced Polymers - Fahimeh Yavartanoo; Chang-Soo Kim; Thomas H.-K. Kang (International Journal of Concrete Structures and Materials)
Abstract Using fiber-reinforced polymer (FRP) has gained widespread acceptance as an effective method for strengthening masonry walls in seismic zones. This research focuses on analyzing the in-plane behavior of dry-stack masonry walls reinforced with embedded FRP bars, providing a cost-efficient solution. Three reinforcement layouts, including horizontal, vertical, and diagonal, each with varying numbers of bars, were investigated. Alongside various FRP materials such as carbon, aramid, and glass fibers, the study also encompasses titanium and stainless steel bars to ensure a comprehensive assessment. Two-dimensional nonlinear finite element models were proposed using ABAQUS software, employing a micro-modeling strategy to investigate the performance of retrofitted walls. The modeling approach was validated by comparing it with existing experimental data. The lateral response of the walls under vertical loads was evaluated using pushover and cyclic analysis methods for different arrangements and materials of bars to find the most efficient model. The findings indicated that vertically aligned S-Glass FRP outperforms other models in enhancing wall overstrength, stiffness hardening, and energy dissipation capacity.